2022
DOI: 10.3389/fpubh.2022.820643
|View full text |Cite
|
Sign up to set email alerts
|

Income Disparities in Cancer Screening: A Cross-Sectional Study of the Korean National Health and Nutrition Examination Survey, 2013–2019

Abstract: BackgroundCancer is one of the leading chronic diseases, which causes premature mortality in Korea. Early detection has been reported to be associated with reduced mortality and morbidity. Consistent evidence reports that lower screening rates are associated with socioeconomic-based disparities. This study aimed to examine income-related disparities in cancer screening services and to analyze the association between utilization of cancer screening and individual characteristics, including income levels.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…44 However, the lower income group showed a higher cancer-specific mortality rate for most cancers, which could result from poorer access to screening and appropriate treatment, leading to a higher proportion of late-stage cases. 45,46 We found that individuals with unhealthy lifestyles had poorer health outcomes, as in previous studies. 27,28 Multiple unhealthy behaviors (including smoking, alcohol drinking, physical inactivity, unhealthy diet, abnormal sleep duration, and television viewing time) were found to be strongly associated with CVDs and all-cause mortality 28 ; in addition, healthy lifestyle (non-smoking, non-drinking, physical activity, maintaining a healthy diet, and a waist-to-hip ratio <0.90 for men and <0.85 for women) reduced liver cancer risk by 43% in the Chinese.…”
Section: Discussionsupporting
confidence: 81%
“…44 However, the lower income group showed a higher cancer-specific mortality rate for most cancers, which could result from poorer access to screening and appropriate treatment, leading to a higher proportion of late-stage cases. 45,46 We found that individuals with unhealthy lifestyles had poorer health outcomes, as in previous studies. 27,28 Multiple unhealthy behaviors (including smoking, alcohol drinking, physical inactivity, unhealthy diet, abnormal sleep duration, and television viewing time) were found to be strongly associated with CVDs and all-cause mortality 28 ; in addition, healthy lifestyle (non-smoking, non-drinking, physical activity, maintaining a healthy diet, and a waist-to-hip ratio <0.90 for men and <0.85 for women) reduced liver cancer risk by 43% in the Chinese.…”
Section: Discussionsupporting
confidence: 81%
“…This finding reflects disparities in cancer screening participation among people from lower income communities. [28][29][30][31] Other studies in a range of populations have found similar associations between stage at diagnosis for cancers with screening programs and SES, particularly for colorectal cancer 20,32,33 and breast cancer. 20,34,35 These disparities exist even in countries with publicly funded health coverage because financial concerns may affect when and whether individuals with lower incomes access health services.…”
Section: Discussionmentioning
confidence: 73%
“…Finally, the study population was included in the national cancer screening program. Considering the different characteristics of people who underwent cancer screening and those who did not receive cancer screening, the results based on participants in the national cancer screening program would be affected by selection bias 35 . However, when we compared cancer incidence rates in our study population with the Korean national cancer statistics, the incidence rates were comparable, suggesting minimal selection bias.…”
Section: Discussionmentioning
confidence: 90%